1989
DOI: 10.1016/0735-1097(89)90621-9
|View full text |Cite
|
Sign up to set email alerts
|

Sustained nonoxidative glucose utilization and depletion of glycogen in reperfused canine myocardium

Abstract: Ischemically injured reperfused myocardium is characterized by increased 18F-fluorodeoxyglucose uptake as demonstrated by positron emission tomography. To elucidate the metabolic fate of exogenous glucose entering reperfused myocardium, D-[6-14C] glucose and L-[U-13C] lactate were used to determine glucose uptake, glucose oxidation and the contribution of exogenous glucose to lactate production. The pathologic model under investigation consisted of a 3 h balloon occlusion of the left anterior descending corona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(44 citation statements)
references
References 21 publications
1
43
0
Order By: Relevance
“…This rate was chosen to raise the steady-state 13 C enrichments of plasma glucose and its myocardial intermediary metabolite pools to levels sufficient for precise measurement without raising plasma glucose concentration. As originally demonstrated by Lewandowski and others, 4,9 during continuous infusion of D- [1][2][3][4][5][6][7][8][9][10][11][12][13] C]glucose, the myocardial pyruvate pool accumulates [3-13 C]pyruvate in proportion to that fraction of total glycolytic substrate contributed by circulating glucose relative to other carbon sources (eg, 12 C-glycogen). Myocardial concentrations of pyruvate are generally too low for its 13 C enrichment to be measured in small samples, but pyruvate is in equilibrium through transaminase reactions with the larger alanine pool.…”
Section: Experimental Protocolsmentioning
confidence: 99%
See 3 more Smart Citations
“…This rate was chosen to raise the steady-state 13 C enrichments of plasma glucose and its myocardial intermediary metabolite pools to levels sufficient for precise measurement without raising plasma glucose concentration. As originally demonstrated by Lewandowski and others, 4,9 during continuous infusion of D- [1][2][3][4][5][6][7][8][9][10][11][12][13] C]glucose, the myocardial pyruvate pool accumulates [3-13 C]pyruvate in proportion to that fraction of total glycolytic substrate contributed by circulating glucose relative to other carbon sources (eg, 12 C-glycogen). Myocardial concentrations of pyruvate are generally too low for its 13 C enrichment to be measured in small samples, but pyruvate is in equilibrium through transaminase reactions with the larger alanine pool.…”
Section: Experimental Protocolsmentioning
confidence: 99%
“…Samples were then stored for 2 hours to allow complete decay of 13 N (t 1/2 ϭ10 minutes) and recounted for residual 18 F (t 1/2 ϭ110 minutes). 13 N counts per gram were …”
Section: Regional Myocardial Blood Flow and Glucose Uptakementioning
confidence: 99%
See 2 more Smart Citations
“…[4][5][6][7] The increase in glucose ; by an investigative group uptake in reperfused myocardium 24 hours after reperfusion reflects at least in part enhanced nonoxidative glucose utilization. 3 Qualitative evaluation of glucose utilization in chronically instrumented dogs demonstrated that glucose metabolism remained significantly higher in postischemic myocardium relative to remote normal myocardium 1 week after reperfusion.2 Quantitative measurements in chronically instrumented dogs demonstrated that relative enhancement of glucose metabolism in postischemic myo-cardium was observed only when glucose metabolism in normal myocardium was low. 1 Depressed oxygen consumption has also been demonstrated in reperfused myocardium, both acutely4,8-10 and 24 hours after reperfusion,4 although it should be noted that others have found normal'1 or even increased12 oxygen consumption in postischemic myocardium.…”
mentioning
confidence: 99%